Impact of Educational Intervention on Knowledge, Attitude and Practice Towards Diabetes Mellitus among the Students of Pharmacy Profession of a College - Dey, Tiyasa; Gupta, Kunal; Sen, Suchandra (Indian Journal of Pharmacy Practice)
Background: The ever-increasing rise in the number of diabetic patients is alarming and needs immediate tackling as it is on the brink of reaching epidemic proportions. An interesting trend is the spurt in cases among the young adults, mainly for lifestyle reasons. An improvement in the awareness and the understanding of the disorder is a step towards reducing the incidence of the disease. As healthcare provider, pharmacist advice patients and members of the public on pharmaceutical matters pertaining to illnesses and medications. Materials and Methods: The present study evaluated the knowledge, attitude and practice of pharmacy students towards diabetes mellitus. A Google form questionnaire was prepared and distributed among the students. A total of 160 respondents were collected and educational intervention was administered to those students. Pre and post-intervention scores were statistically analyzed. Results: It was observed that there was a significant improvement in the three dimensions-knowledge, attitude and practice after the intervention. Conclusion: Regular educational interventions are needed to spread awareness of the disease and check its spread.
Keywords: Knowledge; Attitude; Practice; Diabetes mellitus